2018
DOI: 10.1016/j.ecolecon.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A Household's Burden – The Embodied Resource Use of Household Equipment in Germany

Abstract: We use cluster analysis and material flow accounting to describe patterns of resource use in German households. Data on socio-demographic characteristics, and expenditures on fuel, electricity and household equipment allow for a differentiation of seven different household types. The corresponding resource use, expressed in Material Footprint per person and year, is calculated based on cradle-to-gate material flows of average household goods. Our results show that patterns of resource use are mainly driven by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…This could be partly explained by the energy requirement to operate these products, but also by the tendency for materialistic consumer lifestyles to have higher carbon footprints overall, as a sum of footprints across all consumption domains. The findings in this study on the impacts of materialistic lifestyles with multiple product ownership confirmed the relevance of ownership of household equipment [36]. To confirm the absence of multicollinearity, the variance influence factor (VIF) test of independent variables was used for each model, which revealed that none of the above models had multicollinearity problems based on the criteria of a VIF not greater than 10.…”
Section: The Individual Determinants Of High-carbon Households In Japansupporting
confidence: 71%
See 2 more Smart Citations
“…This could be partly explained by the energy requirement to operate these products, but also by the tendency for materialistic consumer lifestyles to have higher carbon footprints overall, as a sum of footprints across all consumption domains. The findings in this study on the impacts of materialistic lifestyles with multiple product ownership confirmed the relevance of ownership of household equipment [36]. To confirm the absence of multicollinearity, the variance influence factor (VIF) test of independent variables was used for each model, which revealed that none of the above models had multicollinearity problems based on the criteria of a VIF not greater than 10.…”
Section: The Individual Determinants Of High-carbon Households In Japansupporting
confidence: 71%
“…Households with this factor tended to use large amounts of fuel at home for heating but might also consume less meat and more fruit and vegetables. These underlying lifestyle factors confirmed the relevance of carbon-intensive leisure activities, car driving, home energy consumption, meat and dairy product consumption [10], and ownership and use of goods [36] for addressing environmental impacts of consumer lifestyles. The identified lifestyle factors were beyond a single product category or domain, as illustrated by a factor referring to car driving, leisure, and product consumption.…”
Section: The Lifestyle Factors Contributing To Carbon Footprints In Vsupporting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, information from small-scale studies cannot be extrapolated to approximate broader consumption patterns. Some authors identify that it is important to provide households with information that can help them make more environmentally responsible choices, but certain groups may need more support or even incentives to adopt more sustainable lifestyles [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Its indicator Material Footprint can also be adapted to the currently suggested SDG 12 indicator with the same name. Recent methodological developments make use of improved LCA data [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%